CuFeO2–CeO2 nanopowder catalyst prepared by self-combustion glycine nitrate process and applied for hydrogen production from methanol steam reforming. (11th June 2020) - Yu, Chung-Lun; Sakthinathan, Subramanian; Hwang, Bae-Yinn; Lin, Sheng-Yi; Chiu, Te-Wei; Yu, Bing-Sheng; Fan, Yu-Jui; Chuang, Chenghao
Abstract: Hydrogen (H2 ) is being considered as an alternate renewable energy carrier due to the energy crisis, climate change and global warming. In the chemical industry, hydrogen production is mainly accomplished by the steam reforming of natural gas. In the present study, CuFeO2 –CeO2 nanopowder catalyst with a heterogeneous delafossite structure was prepared by the self-combustion glycine nitrate process and used for steam reforming of methanol (SRM). The precursor solution was fabricated from Cu–Fe–Ce metal-nitrate mixed with glycine and an aqueous solution. The prepared CuFeO2 –CeO2 nanopowder catalyst was studied by different physical and chemical characterization techniques. The prepared CuFeO2 –CeO2 nanopowder catalyst was immensely porous with a coral-like structure. The BET surface area measurement revealed that the specific surface area of as-combusted CuFeO2 –CeO2 nanopowder varied from 5.6248 m 2 /g to 19.5441 m 2 /g. In addition, the production rate of CuFeO2 –CeO2 was improved by adding CeO2 and adjusting the feeding rate of the methanol. The highest H2 generation rate of the CuFeO2 –CeO2 catalyst was 2582.25 (mL STP min −1 g-cat −1 ) at a flow rate of 30 sccm at 400 °C. Hence, the high specific surface area of the 70CuFeO2 –30CeO2 nanopowder catalyst and the steam reforming process could have a very important industrial and economic impact. Highlights: CuFeO2 –CeO2 nanopowder prepared by a self-combusted glycine nitrate process. The BET surface area of CuFeO2 _CeO2 varied from 5.6248 m 2 /g to 19.5441 m 2 /g. The CuFeO2 –CeO2 nanopowder was applied for the steam reforming of methanol. The 70CuFeO2 –30CeO2 exhibited H2 production rate of 2582.25 (mL STP min −1 g-cat −1 ). High H2 production rate exhibited in flow rate of 30 sccm at 400 °C.